Time-Delay Control for Integrated Missile Guidance and Control - Park, Bong-Gyun; Kim, Tae-Hun; Tahk, Min-Jea (International journal of aeronautical and space sciences, 2011)
In this paper, integrated missile guidance and control systems using time-delay control (TDC) are developed. The next generation missile requires that an interceptor hits the target, maneuvering with small miss-distances, and has lower weight to reduce costs. This is possible if the synergism existing between the guidance and control subsystems is exploited by the integrated controller. The TDC law is a robust control technique for nonlinear systems, and it has a very simple structure. The feature of TDC is to directly estimate the unknown dynamics and the unexpected disturbance using one-step time-delay. To investigate the performance of the integrated controller, numerical simulations are performed as the maneuver of the target. The results show that the integrated guidance and control system has a good performance. KCI Citation Count: 2